2016
DOI: 10.1185/03007995.2016.1162773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vildagliptin versus saxagliptin on daily acute glucose fluctuations in Chinese patients with T2DM inadequately controlled with a combination of metformin and sulfonylurea

Abstract: Objective The present study aimed to compare the effects of the dipeptidyl peptidase-4 (DPP-4) inhibitors vildagliptin and saxagliptin on 24 hour acute glucose fluctuations in Chinese patients with type 2 diabetes mellitus (T2DM) inadequately controlled with a combination of metformin and sulfonylurea. Research design and methods This was a 24 week, prospective, randomized, open-label, active-controlled study. Patients (N = 73) with T2DM who had inadequate glycemic control (HbA1c 7.0%-10.0%) with a stable dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
5
0
2
Order By: Relevance
“…Previous studies have demonstrated that saxagliptin therapy in Asian patients is well tolerated in treatment‐naive patients, in combination with metformin, and in combination with other oral glucose‐lowering agents . A potential benefit of using a DPP‐4 inhibitor as add‐on therapy over other antidiabetes agents is that the activity of this class of drugs on insulin secretion is glucose‐dependent, and DPP‐4 inhibitors are therefore associated with a low risk of hypoglycaemia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that saxagliptin therapy in Asian patients is well tolerated in treatment‐naive patients, in combination with metformin, and in combination with other oral glucose‐lowering agents . A potential benefit of using a DPP‐4 inhibitor as add‐on therapy over other antidiabetes agents is that the activity of this class of drugs on insulin secretion is glucose‐dependent, and DPP‐4 inhibitors are therefore associated with a low risk of hypoglycaemia .…”
Section: Discussionmentioning
confidence: 99%
“…Asian patients is well tolerated in treatment-naive patients, 6 in combination with metformin, 7,13,14 and in combination with other oral glucose-lowering agents. 15,16 A potential benefit of using a DPP-4…”
Section: Previous Studies Have Demonstrated That Saxagliptin Therapy Inmentioning
confidence: 99%
“…Вілдагліптін (LAF237) -високоселективний інгібітор ДПП-4, що перешкоджає швидкому руйнуванню ГПП-1 і ГІП, у результаті чого фізіологічна дія інкретинових гормонів на клітини острівцевого апарату підшлункової залози продовжується. Тривалість такої дії залежить в основному від того, наскільки повного пригнічення вдається досягнути [7]. З огляду на кристалічну структуру хімічно споріднених піролідинових нітрилів ігібіторів ДПП-4 є підстави вважати, що вілдагліптин є повільним субстратом для ДПП-4, який блокує інактивацію ГПП-1 і ГІП протягом 24 годин і утворює зворотну ковалентну імінефірну сполуку з активною сериновою ділянкою ДПП-4, що сприяє протонуванню сусіднього амінокислотного залишку й викликає морфологічні зміни ділянки зв'язування.…”
Section: можливості вілдагліптину в оптимальному контролі цукрового дunclassified
“…Терапия вилдаглиптином в сравнении с ситаглиптином и саксаглиптином ассоциирована с меньшей САКГ. К тому же при приеме вилдаглиптина отмечено большее снижение уровня глюкагона, а гликемия пациентов дольше находилась в заданных диапазонах [50,51].…”
Section: метаанализы и сравнительные исследованияunclassified